2023
DOI: 10.21070/pedagogia.v11i1.1486
|View full text |Cite
|
Sign up to set email alerts
|

Community Resistance to Online Learning Policies During Covid-19 Pandemic in Education

Abstract: The online learning policy, which is believed to be the only way out of overcoming learning and accelerating the end of the transmission of the Covid-19 virus, has been widely rejected. In Indonesia, various community groups do not support and even protest the implementation of online learning. This paper aims to analyze the forms and factors of community resistance to online learning policies. This study uses a qualitative descriptive technique. The discourse of denial in online news forms the basis for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, in some other parts of the world, resistance to fully online learning environments has emerged: for instance, research conducted in Ontario found that "significant negative effects regarding the move to the fully online environment were recorded by some participant groups" (McGravey and vanOostveen, 2022). Similarly, Wigati et al (2023) explore the "rejection" and "refusal" of the pandemic-induced transition to online teaching and learning in the Indonesian context, citing "the tension in the relationship between the people and the state" as the underlying motivation-flagging the need for education communities to feel that they exist within a democracy, both on the level of the education system and on the level of wider governance.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some other parts of the world, resistance to fully online learning environments has emerged: for instance, research conducted in Ontario found that "significant negative effects regarding the move to the fully online environment were recorded by some participant groups" (McGravey and vanOostveen, 2022). Similarly, Wigati et al (2023) explore the "rejection" and "refusal" of the pandemic-induced transition to online teaching and learning in the Indonesian context, citing "the tension in the relationship between the people and the state" as the underlying motivation-flagging the need for education communities to feel that they exist within a democracy, both on the level of the education system and on the level of wider governance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the Society 5.0 era, the curriculum has become adaptive, tailored to society and industry needs, emphasizing skills such as problem-solving, creativity, and adaptability. The role of teachers has also evolved, with educators acting more as agents of change, facilitators, and mentors in the learning process rather than simply as sources of knowledge (Nofridasari & Hidayati, 2024;Wigati et al, 2023).…”
Section: A Introductionmentioning
confidence: 99%